Critical literacies and gender studies : navigating media, education, and civic engagement for social justice - Amaral, Inês; Flores, Ana Marta M.; Basílio de Simões; Antunes, Eduardo (Emerald Publishing Limited, 2025)
In today's increasingly digital media landscape, enhancing critical literacy and fostering civic engagement is crucial for addressing gender disparities and broader inequalities within education and public life. Critical Literacies and Gender Studies explores the intersections of media literacy, gender studies, and civic participation, offering theoretical insights and practical strategies to challenge dominant power structures and advocate for gender equity. It highlights the importance of integrating critical literacies into educational curricula, combating misinformation, and fostering an inclusive digital environment. Topics include European research on digital citizenship and gender equality, the regulation of social platforms, and mediated intimacies. Critical Literacies and Gender Studies provides an interdisciplinary framework for analysing how media practices shape societal norms, education, and civic life.
Keywords: Literacy.; Service learning.; Social justice.; Education -- Philosophy, Theory & Social Aspects.; Philosophy and theory of education.; elektronické knihy; electronic books